The Consequences of Early Matrimony: A Qualitative Inquiry into Women's Mental Health and Socio-economic Challenges - Aftab, Muhammad; Fayyaz, Ayesha (MID Publisher International, 2024)
This study examines the complex relationship between early marriage and its effects on the mental health of young married women in Pakistan. Defining early marriage as a union in which at least one of the parties is under the age of 18, this research sheds light on the multifaceted consequences of such marriages, particularly for women's mental health and subsequent child development. Using qualitative research methods, in-depth interviews with a carefully selected sample of women served as the basis for this study. People in this category are those who were married between the ages of 16 and 17 and are currently older than 30. By examining the social, physical, emotional, and economic ramifications of early marriage throughout the course of their lives, this demographic sample offers a longitudinal view on its consequences. A great deal of attention is paid to women who were married in the 1990s, and the difficulties they faced are examined in light of various sociodemographic characteristics. Wealth index, occupation, education level, resource management in the home, freedom to make health-related decisions, geography, media exposure, and health insurance coverage are some of these variables. According to the study, these variables are linked to early marriage's prevalence and the long-term consequences it has on women's social, emotional, and physical health. The study also emphasizes the part postponed marriage and sociodemographic traits plays in reducing the prevalence of early marriage like greater education levels and better employment possibilities are crucial in lowering the incidence of early marriage.